Prognostic significance of lymphocytic foci composition in minor salivary gland biopsies for severe disease flare and severity in Sjögren’s syndrome: a 3-year follow-up cohort study - Park, Hye-Sang; Martínez-Martínez, Laura; Magallares López, Berta; Castellví, Ivan; Moya, Patricia; Codes-Mendez, Helena; Hernandez Sosa, Nerea; Diaz-Torne, Cesar; Laiz, Ana; Sainz, Luis; Tandaipan, Jose Luis; Mariscal, Anaís; et al. (Frontiers in Immunology, 2024)
Introduction: Ambispective cohort study evaluating the prognostic significance of lymphocytic foci and its lymphoid composition in minor salivary gland biopsies (MSGB) for short term disease flare and severity in Sjögren's Syndrome (SS).Methods Inclusion criteria comprised individuals meeting ACR/EULAR 2016 criteria who underwent MSGB with an infiltration of more than 50 lymphocytes and received clinical diagnosis between September 2017 and December 2018. Patients with inadequate biopsy samples were excluded. The number of lymphocytic foci and their lymphoid composition in MSGB were assessed using immunofluorescence staining. Major organ damage and improvements in the EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) were measured. Statistical analyses, including Cox and linear regressions, were conducted.Results: Seventy-eight patients with at least one lymphocytic foci were included in the study. The presence of higher T cell counts in lymphocytic foci in MSGB was associated with severe disease flare, and a logarithmic transformation of T cell count indicated increased risk (HR 1.96, 95% CI 0.91-4.21). Improvements in ESSDAI were associated with higher total lymphocyte count, T and B cell numbers in the lymphoid composition of the lymphocytic foci. Seropositive patients exhibited higher T CD4+ cell numbers. Correlation analysis showed negative associations between age and lymphocytic foci, as well as its T cell count. Positive correlations were observed between antinuclear antibody (ANA) titers and total lymphocyte numbers. Discussion: Patients with a higher number of T cells in the lymphocytic infiltrates of lymphocytic foci may have two-fold risk of severe disease flare. The number of B cells and T CD4+ cells in the lymphocytic infiltrates of lymphocytic foci showed a weak but positive relation with ESSDAI improvement during follow-up. Age and seropositivity appear to influence lymphoid composition of the lymphocytic foci.